(3QSGdI Edi GdSGOI aj GdOYhI dWGYI hdi GdMb GdEeGe GdbGFe GdefJXQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdgg GdMGce GdefRg Yf GdJfRjg hJhSdJ Edjg HYHOg GdgGOi GdbGFe HMbjbI GdJhMjO hGdJCdjg ef GdYHO GdfGUM HgGA GdOjf s
(3BNQgG (B:s
(3hef HYO cJH gPG GdSaQ YQVJ ehGfY bWYJ GdWGgQI Yf GdSaQ hCjVkG jchf Pdc HYO hVhM bHhd GdSGOI JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B67s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis